Design and simulation of temperature distribution of industry size incubator for poultry hatching - Nurhanis Najiha Omar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The object of this thesis is to describe a method for finding the temperature distribution in the industrial incubator that containing a heat source distributed. There are three important cases to build up the effective product of industry incubator which are temperature distribution inside, the humidity and the ventilation. This research focuses on the study of temperature distribution inside the incubator because temperature is the main issue to design and simulate of an incubator.